BASES AND FORMS OF PARTICIPATION OF THE SECURITY FORCES, JUDICIAL AND LAW ENFORCEMENT BODIES OF UKRAINE IN COUNTERING SMUGGLING - Krylovetskiy, A. (Honor and Law, 2020)
The article analyzes the system of state bodies for combating smuggling. According to the most common classification of state bodies by the criterion of the breadth of competence, there are state bodies of general and special competence. If we adhere to this classification, the general bodies of counteraction to smuggling are state bodies of general competence, which are the Verkhovna Rada, the Cabinet of Ministers, the President of Ukraine. The bodies of special competence are the security forces, judicial and law enforcement agencies. It is determined that there is no single definition of the concept of law enforcement agencies in the legislation, it is provided in various regulations. Anti-smuggling law enforcement agencies are state bodies that implement the law enforcement and law enforcement function of the state, which have the authority to apply measures to detect, prevent, eliminate crimes and other offenses related to smuggling, have the right to bring to justice those responsible for such offenses, and may, if necessary, apply state coercion. The participation of these bodies in combating smuggling is realized through appropriate forms of cooperation. The form of interaction between security forces, judicial and law enforcement agencies in combating smuggling means the outwardly expressed organizational and procedural-legal coordinated activities of various parts of the system of public authorities in the field of combating smuggling, carried out within their competence. All forms of cooperation in the field of combating smuggling can be divided into two major groups: 1) procedural and legal forms, which are provided by criminal and administrative procedural law; 2) organizational and tactical forms that do not contradict the criminal and administrative procedural law, but may be provided by bylaws. Laws and bylaws are the basis for interaction between security forces, judicial and law enforcement agencies. By-laws include, first of all, joint orders, interaction plans, interdepartmental decisions, instructions. It is concluded that it is necessary to amend the legislation in this area.